Factors Related to Respiratory Symptoms among Workers of A Highway District in Eastern Region - Inthaphan, Jutharat; Kaewboonchoo, Orawan; Boonyamalik, Plernpit; Chanyasanha, Charnchudhi (Journal of Public Health Nursing, 2021)
Workers of highway districts are exposed to a wide variety of chemical substances, including asphalt which may affect workers’ respiratory systems. This study aimed to investigate factors related to respiratory symptoms among 102 workers of a highway district in Eastern region of Thailand. A Cross-sectional study design with self-administered questionnaire was applied to collect studied data. Multiple Logistic Regression analysis was performed to examine the relationship between personal characteristics and work factors with respiratory symptoms. Results revealed that the prevalence of respiratory symptoms among workers of highway district in the eastern region of Thailand was 18.6%. Factors related to respiratory symptoms were work at department with PAH exposure (ORadj=5.53, 95%CI=1.63-18.74), working more than 10 years (ORadj= 4.24, 95% CI=1.17-15.31) and comorbidity with diabetes and hypertension (ORadj=4.42, 95% CI=1.34-14.54). Study results suggested that department of highway and health care related agencies should take action to prevent PAH exposure to reduce risk of respiratory symptoms among road paving asphalt workers. Use of suitable personal protective equipment (PPE) should be implemented following the training of workers in the proper use of PPE.